Observations of Wave‐Breaking Direction and Energy Spread - Bernard Akaawase; Leonel Romero; Alvise Benetazzo (Geophysical Research Letters, 2025)
Abstract Surface waves are important for remote sensing, air–sea exchange, and underwater acoustics. The short gravity wave spectrum is azimuthally broad and bimodal. However, widely used wave models fail to reproduce the degree of observed spreading and azimuthal bimodality. Recent studies show that an azimuthally narrow spectral breaking dissipation due to long‐wave short‐wave modulation significantly improves model performance, highlighting the importance of better understanding the directionality of breaking kinematics. We utilized visible stereo imagery to investigate the directional wave‐breaking kinematics relative to the energy spectrum under aligned and misaligned winds and dominant waves. The results show that the statistical distribution of wave‐breaking kinematics closely aligns with the direction of the dominant waves and is azimuthally unimodal and narrower than the bimodal energy spectrum. These findings confirm the importance of exploring the directionality of breaking to improve our understanding of the spectral energy balance and spectral wave models within the short‐gravity range.